2023
DOI: 10.3389/fpubh.2023.1124206
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with HPV vaccine acceptability and hesitancy among Black mothers with young daughters in the United States

Abstract: IntroductionCompared to other-race peers, Black women are disproportionately impacted by human papillomavirus [HPV] infection, related health outcomes, and cervical cancer mortality as a result of suboptimal HPV vaccine uptake during adolescence. Few studies in the United States have examined psychosocial determinants of HPV vaccine acceptability and hesitancy among Black parents. The current study integrated the health belief model and the theory of planned behavior to evaluate the extent to which psychosocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…Indeed, parents who had received a recommendation and those who had acquired information from physicians were more likely to have vaccinated their child and to intend to vaccinate their child with all recommended vaccinations. These findings highlight the central role played by physicians in the parents’ education and decisions and confirm previous studies that showed the positive influence of receiving a physicians’ recommendation on the populations’ attitudes and behaviors with a higher vaccination willingness and coverage [ 15 , 19 , 21 , 22 , 23 , 24 ]. However, it is necessary to underline that only one-fourth of the sample had received a recommendation from physicians and, therefore, it is imperative to provide educational activities to the healthcare workers particularly aiming to raise their awareness about vaccines’ efficacy and to recommend vaccinations for children with chronic medical conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, parents who had received a recommendation and those who had acquired information from physicians were more likely to have vaccinated their child and to intend to vaccinate their child with all recommended vaccinations. These findings highlight the central role played by physicians in the parents’ education and decisions and confirm previous studies that showed the positive influence of receiving a physicians’ recommendation on the populations’ attitudes and behaviors with a higher vaccination willingness and coverage [ 15 , 19 , 21 , 22 , 23 , 24 ]. However, it is necessary to underline that only one-fourth of the sample had received a recommendation from physicians and, therefore, it is imperative to provide educational activities to the healthcare workers particularly aiming to raise their awareness about vaccines’ efficacy and to recommend vaccinations for children with chronic medical conditions.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, these results could be used to better target the development of approaches aimed at increasing the acceptance of the RSV vaccine. These factors have been studied for other recommended vaccinations [15][16][17][18], but few surveys have been conducted to explore the acceptance of a future RSV vaccine among pregnant women [19,20] and healthcare workers (HCWs) [21]. Therefore, the primary outcome of this study was to assess parents' willingness to vaccinate their children with the RSV vaccine and to identify the key predictors of this intention.…”
Section: Introductionmentioning
confidence: 99%